Pre-competition nutrition guidelines (1999)
Here are some recommendations for eating before a competition. However, remember that everyone is different in their tolerance to foods - some people, depending on their sport, can eat almost anything just before they compete, while others have a more sensitive stomach. It's best to experiment with different foods and meal timing before practice sessions, so you'll know what foods to eat and when to eat them before a competition. Don't experiment with something new the day of a big event!